Audit as a Tool for Preventing Bankruptcy Risks and Evaluating Development Prospects for Tourism Industry Companies - ALIMBEKOVA, Gaukhar; KANTARBAYEVA, Shyryn; ABDILDIN, Srym; YERZHANOVA, Alma Mukhtarovna; KYDYRBAYEVA, Sholpan (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021, 2021)
The purpose of the study is to explore the possible courses for increasing the value of audits in preventing bankruptcies in the tourism industry. The key method of the study is the expert survey that 108 Kazakh companies working in the tourism and travel industry have taken part in. The results of the survey show that currently, the risk of bankruptcy among travel companies is fairly high. The results obtained indicate that currently, there is a significant demand from the tourism industry for a broader scope of the audit.